A press achieved : the emergence of Auckland University Press, 1927-1972, with a brief epilogue to 1986 and a list of Auckland University College, University of Auckland, and Auckland University Press publications, 1927-2000 /: the emergence of Auckland University Press, 1927-1972, with a brief epilogue to 1986 and a list of Auckland University College, University of Auckland, and Auckland University Press publications, 1927-2000. (2013) - Unknown
No abstract available